Increasing Motivation and Learning Achievement of Fiqh Through the STAD Type Cooperative Learning Model - Novi Rasanti; Imam Tabroni; Suprianto; Dian Wahyuni (Indonesian Journal of Applied and Industrial Sciences (ESA), 2022)
Achievement of learning objectives cannot be separated from the role of a teacher. Teachers should be a motivator for their students, so that their potential is fully realized developed. Teachers should be able to create a classroom climate that is conducive to learning materials proposed for creative teachers will be able to manage the class that student achievement can be optimized. This study aims to determine how to improve students' motivation and achievement through cooperative learning models of STAD (Student Team Achievement Division). This research is a classroom action research. The subjects were students of class Student MA Al-Asy-ary Purwakart a in the academic year 2022/2023. The results of this study showed an increase learning motivation significantly.